2008
DOI: 10.1073/pnas.0706296105
|View full text |Cite
|
Sign up to set email alerts
|

Antigen kinetics determines immune reactivity

Abstract: A current paradigm in immunology is that the strength of T cell responses is governed by antigen dose, localization, and costimulatory signals. This study investigates the influence of antigen kinetics on CD8 T cell responses in mice. A fixed cumulative antigen dose was administered by different schedules to produce distinct dose-kinetics. Antigenic stimulation increasing exponentially over days was a stronger stimulus for CD8 T cells and antiviral immunity than a single dose or multiple dosing with daily equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
131
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(144 citation statements)
references
References 51 publications
(44 reference statements)
9
131
0
Order By: Relevance
“…By contrast, during "acute" viral infections, the majority of infectious virus is often cleared by 7 days, but residual antigen/ viral nucleic acids can often be detected for 4 to 8 weeks, with clear effects on the immune response (103)(104)(105). Persistent antigen/inflammation exposure in draining LNs over periods of at least several days can be important for maximizing the immune response, enhancing the differentiation of follicular Th cells (106,107), enhancing GC induction (35), and producing an optimal cytokine milieu (108). The duration and magnitude of antigen and adjuvant exposure during priming of naive lymphocytes or boosting of memory cells is known to play a significant role in determining the degree of clonal expansion (109)(110)(111), fate decisions between different functional phenotypes (Th subsets or plasma cells versus memory cell differentiation of B cells; refs.…”
Section: Programming Vaccine Kineticsmentioning
confidence: 99%
“…By contrast, during "acute" viral infections, the majority of infectious virus is often cleared by 7 days, but residual antigen/ viral nucleic acids can often be detected for 4 to 8 weeks, with clear effects on the immune response (103)(104)(105). Persistent antigen/inflammation exposure in draining LNs over periods of at least several days can be important for maximizing the immune response, enhancing the differentiation of follicular Th cells (106,107), enhancing GC induction (35), and producing an optimal cytokine milieu (108). The duration and magnitude of antigen and adjuvant exposure during priming of naive lymphocytes or boosting of memory cells is known to play a significant role in determining the degree of clonal expansion (109)(110)(111), fate decisions between different functional phenotypes (Th subsets or plasma cells versus memory cell differentiation of B cells; refs.…”
Section: Programming Vaccine Kineticsmentioning
confidence: 99%
“…In addition, these signaling molecules can influence the maturation and migration of antigen presenting cells towards the lymph nodes (Koutsonanos et al 2013). If these processes were included in the model, the release rate may prove to influence the evoked immune response when a sustained period is simulated, since it has been reported that a vaccination regime over many days can increase the response (Johansen et al 2008). However, with the present static cell density, no long term processes could be predicted and, as a result, the release rate did not have any influence on cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…Flushing of extracellular vaccine components from the LN may not limit the exposure of antigen-specific lymphocytes to antigen because nucleic acid vaccines transfect cells on injection (leading to sustained local antigen production) and subunit antigens are internalized by APCs and B cells for subsequent processing/ presentation over several days (14,15). However, vaccine clearance might particularly limit the effectiveness of molecular adjuvants because inflammatory signals [such as Toll-like receptor (TLR) a] are most effective when provided continuously for several days (13,16,17).We hypothesized that combining i.LN vaccination with controlled release biomaterials for adjuvant delivery could allow the inflammatory milieu of LNs to be tailored over defined periods. To test this idea, we employed nonsurgical LN injection of antigen mixed with biodegradable poly(lactide-co-glycolide) microparticles (MPs) or nanoparticles (NPs) encapsulating the TLR3 agonist poly(inosinic:cytidylic acid) (polyIC), a potent molecular adjuvant known to promote CD4 þ T-cell responses and drive cross-presentation of soluble antigen to CD8 þ T cells (18).…”
mentioning
confidence: 99%
“…Flushing of extracellular vaccine components from the LN may not limit the exposure of antigen-specific lymphocytes to antigen because nucleic acid vaccines transfect cells on injection (leading to sustained local antigen production) and subunit antigens are internalized by APCs and B cells for subsequent processing/ presentation over several days (14,15). However, vaccine clearance might particularly limit the effectiveness of molecular adjuvants because inflammatory signals [such as Toll-like receptor (TLR) a] are most effective when provided continuously for several days (13,16,17).…”
mentioning
confidence: 99%
See 1 more Smart Citation